RESTORING SAFETY: AN ATTACHMENT‐BASED APPROACH TO CLINICAL WORK WITH A TRAUMATIZED TODDLER. Issue 1 (30th December 2015) - Ribaudo, Julie
ABSTRACT: This clinical case study explores the integration of infancy research, brain development, attachment theory, and models of infant–parent/child–parent psychotherapy to address the needs of abused and neglected young children placed in foster or adoptive homes. Traumatized children employ defensive strategies to survive when there is no "good enough" caregiver (D.W. Winnicott, 1953, p. 94), and helping professionals can provide therapeutic experiences to develop or restore a child's sense of safety. With the case example of Anthony and his foster/adoptive parents, I illustrate how to manage and contain a traumatized child's terror, rage, and grief through therapeutic sessions with the parent and child together, and supportive parental guidance. I promote attention to the child's ability to self‐integrate and to regulate his own affect, and encourages secure‐base parental responses that facilitate a child's shift toward secure attachment behavior.